PENERAPAN BLENDED LEARNING PADA MATA PELAJARAN PAI MASA PANDEMI DI SMPN 1 KANDAT - Alfina Damatussolah, Dhea (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2021)
Blended Learning is a unique and fun method by combining face to face in the classroom learning and online learning. Blended Learning is able to increase students enthusiasm for learning which was bored to be more fun. The implementations of Blended Learning method is able to motivate students to make it easier to understand the material and be more active to interacting about learning with internet and face to face which makes it easier for them to get exsplanantion material from the teacher. The implementation of Blended Learning in Islamic Religious Education at SMPN 1 Kandat raises various obstacles and opportunities in pandemic era. The use of Blended Learning has been implemented as a school policy with efforts to achieve learning objectives by the teacher, the person in charge, and the flexibility of learning media is an opportunity found during the program. Beside that, technical constraints, limited internet access, and weak assistance are challenges for implementing Blended Learning. These obstacles and opportunities have been manages as well as to achieve an optimal learning, especially in Islamic Religious Education at SMPN 1 Kandat with the Blended Learning method run well and becomes a fun learning for students and teacher.Keywords: Implementation, Blended Learning, Islamic Religious Education